Prescribing Pattern of Corticosteroid in Dermatologic Disorder at Tertiary Care Teaching Hospital in Western Indian - Patel, Zankrut J.; Patel, Dhiren; Patel, Jatin; Patel, Sumit (Universitas Padjadjaran, Indonesia, 2024)
Based on their potent immunosuppressive and anti-inflammatory properties, corticosteroids are essential for treating several skin disorders. Due to their lesser systemic toxicity, topical treatments are recommended. The use of corticosteroids in Indian dermatology practice, however, is not well documented. This study aims to analyze the prescribing patterns of corticosteroids for dermatologic disorders. In the outpatient dermatology department of GCS Hospital, Ahmedabad, a cross-sectional, observational study was conducted for six months, from March 2021 to August 2021. We looked at prevalent skin problems and prescribing patterns in 500 prescriptions. A descriptive statistical analysis was done following the compilation of all the data into Microsoft Office Excel. 169 patients (out of 500) receivedcorticosteroids. There were 53% men and 47% women, respectively. The Papulosquamous illness affected 33% of them. The average number of corticosteroids per prescription was 1.17. Out of 198 prescribed corticosteroids, 163 (82.32%) were topical formulations, and 35 (17.67%) were oral. Among the nine different corticosteroids prescribed, clobetasol was given to 29% of patients. Additionally, 39% of patients received a fixed-dose combination (FDC) of corticosteroids, with clobetasol and salicylic acid being the most commonly used FDC. The average cost of corticosteroids per prescription was 135.18 INR, ranging from 4 INR to 468 INR for 15 days of treatment. The mean cost of corticosteroids was significant compared to other concomitant drugs (P < 0.05). Topical corticosteroids were more commonly prescribed than oral ones, with psoriasis being the most common indication for topical corticosteroids. Clobetasol and mometasone were the most frequently used topical corticosteroids